Prognostic factors of overall survival in children and adolescents enrolled in dose-finding trials in Europe: An Innovative Therapies for Children with Cancer study. (November 2016) - Carceller, Fernando; Bautista, Francisco J.; Jiménez, Irene; Hladun-Álvaro, Raquel; Giraud, Cécile; Bergamaschi, Luca; Dandapani, Madhumita; Aerts, Isabelle; Doz, François; Frappaz, Didier; Casanova, Michela; Morland, Bruce; et al.
Abstract: Objectives: Dose-finding trials are fundamental to develop novel drugs for children and adolescents with advanced cancer. It is crucial to maximise individual benefit, whilst ensuring adequate assessment of key study end-points. We assessed prognostic factors of survival in paediatric phase I trials, including two predictive scores validated in adult oncology: the Royal Marsden Hospital (RMH) and the MD Anderson Cancer Center (MDACC) scores. Methods: Data of patients with solid tumours aged <18 years at enrolment in their first dose-finding trial between 2000 and 2014 at eight centres of the Innovative Therapies for Children with Cancer European consortium were collected. Survival distributions were compared using log-rank test and Cox regression analyses. Results: Overall, 248 patients were evaluated: median age, 11.2 years (range 1.0–17.9); 46% had central nervous system (CNS) tumours and 54% extra-CNS tumours. Complete responses were observed in 2.1%, partial responses in 7.2% and stable disease in 25.9%. Median overall survival (OS) was 6.3 months (95% confidence interval, 5.2–7.4). Lansky/Karnofsky ≤80%, no school/work attendance, elevated creatinine and RMH score ≥1 correlated with worse OS in the multivariate analysis. The RMH and MDACC scores correlated with OS in adolescents (12–17 years), p = 0.002, but not in children (2–11 years). Conclusions: Performance status of 90–100% and school/work attendance at enrolment are strong indicators of longer OS in paediatric phase I trials. Adult predictive scores correlate with survival in adolescents. These findings provide a useful orientation about potential prognosis and could lead in the future to more paediatric-adapted eligibility criteria in early-phase trials. Highlights: We assessed prognostic factors of overall survival (OS) in 248 children and adolescents enrolled in 21 phase I trials between 2000–2014. Performance status of 90–100% and school/work attendance at enrolment were strong indicators of longer OS. Adult predictive scores (RMH and MDACC) correlated with survival in adolescents (12–17 years), but not in children (2–11 years). These findings may orientate about potential prognoses and could lead to paediatric-adapted eligibility criteria in early phase trials.